Prescrire un contraceptif : le rôle de l’institution médicale dans la construction de catégories sexuées - Cécile Ventola (Genre, Sexualité et Société)
Unlike most medical research fields, reproductive health has long focused on women. When contraception became a medical issue in France, this further cemented the perception of it as a female issue. Indeed, the promotion of female medical methods went hand in hand with the discrediting of collaborative contraceptive methods involving both partners, such as withdrawal or condom use. This article aims to analyse how the medicalisation of contraception has reinforced the construction of sexually differentiated roles with regard to reproduction, and specifically the role of the medical profession in defining what is possible and desirable in this sphere. It focuses on health professionals’ representations and attitudes, and the role they play in defining contraceptive standards and gender roles. We conducted 16 semi-structured interviews with contraception providers in Paris and its suburbs in 2012 and 2013. Their representations, for the most part, reflect a gendered perception of individuals and their contraceptive skills, men being associated with sexuality and women with reproduction. This gender differentiation is used as a justification for excluding male methods from contraceptive provision.